The Zen canon : understanding the classic texts - Heine, Steven, 1950-; Wright, Dale Stuart (Oxford University Press, 2004)
Presents a collection of essays, which argue that Zen Buddism actually has a rich and varied literary heritage. Among the significant texts are hagiographic accounts and recorded sayings of individual Zen masters, koan collections and commentaries, and rules for monastic life.